TISSUE AND SPECIES SPECIFIC ESTERASE BANDING PATTERNS OF POMACEA PALUDOSA AND POMACEA CANALICULATA - P. SWAPNA,; T.RAVINDER REDDY, (International Journal of Pharma and Bio Sciences, 2013)
The electrophoretic banding patternof esterases were examined in six different tissues of Pomacea paludosa and Pomacea canaliculata by using different inhibitors viz: pCMB, Paraoxon, Physostigmine, EDTA and AgNo3. Same esterolytic active zones were observed in Ctenidia and Mantle of both species, the maximum number of bands exhibiting in Ctenidia of P.paludosa and P.canaliculata. Species specific differences were observed in some of the regions. Striking substrate – specific reactions were not observed, but based on sensitivity to inhibitors, the tissue esterase of both species classified in to CE, ER, AcE, ArE, AcE and Esdp esterases.